Temporal stimulus properties that attract gaze to the periphery and repel gaze from fixation - Schütz, Alexander C.; Lossin, Felix; Kerzel, Dirk; Justus Liebig University Giessen (My University, 2013)
Humans use saccadic eye movements to fixate different parts of their visual environment. While stimulus features that determine the location of the next fixation in static images have been extensively studied, temporal stimulus features that determine the timing of the gaze shifts received less attention. It is also unclear if stimulus features at the present gaze location can trigger gaze shifts to another location. To investigate these questions, we asked observers to switch their gaze between two blobs. In three different conditions, either the fixated blob, the peripheral blob, or both blobs were flickering. A time-frequency analysis of the flickering noise values, time locked to the gaze shifts, revealed significant phase locking in a time window 300 to 100 ms before the gaze shift at temporal frequencies below 20 Hz. The average phase angles at these time-frequency points indicated that observer´s gaze was repelled by decreasing contrast of the fixated blob and attracted by increasing contrast of the peripheral blob. These results show that temporal properties of both, fixated, and peripheral stimuli are capable of triggering gaze shifts.
Keywords: salience; eye movements; classification images; reverse correlation; time-frequency analysis; temporal contrast sensitivity; wavelet analysis; ddc:150